Athena Athanasiou: Agonistic Mourning: Political Dissidence and the Women in Black - Yannakopoulos, Kostas (Historein, 2019)
Review of Athena Athanasiou. Agonistic Mourning: Political Dissidence and the Women in Black. Edinburgh: Edinburgh University Press, 2017. xii + 348 pp.